Identification of phenolic acids of Pandan anggur (Sararanga sinuosa Hemsley) fruits and their potential antiglycation through molecular docking study - Vita Purnamasari&, Teti Estiasih, Hidayat Sujuti, Simon Bambang Widjanarko (Journal of Applied Pharmaceutical Science, 2021)
Berries are known to contain polyphenols, including phenolic acids, and known Sararanga sinuosa fruits are classified as berries. Identification of phenolic acids of the S. sinuosa fruit extract was done by liquid chromatography coupled to high-resolution mass spectrometry (LC-ESI-Orbitrap-MS). The prediction of the interaction and potency of antiglycation of phenolic acids with the protein surface of human serum albumin (HSA) was carried out by molecular docking. The phenolic acids in the S. sinuosa fruit extracts were syringic acid, isovanillic acid (hydroxybenzoic acid group), chlorogenic acid, 2-hydroxycinnamic acid, sinapinic acid, caffeic acid, and ferulic acid (hydroxycinnamic acid group). Chlorogenic acid, caffeic acid, syringic acid, 2-hydroxycinnamic acid, and sinapinic acid bind to HSA at the FA7 site (subdomain IIA), whereas isovanillic acid and ferulic acid bind to FA6 (between subdomains IIA and IIB) and FA1 sites (subdomain IA), respectively. Phenolic acids that bind to the amino acid residues of Lys195 and/or Lys199, namely chlorogenic acid, caffeic acid, syringic acid, 2-hydroxycinnamic acid, and sinapinic acid, are predicted to occupy the sites for the glycation reaction in HSA. In conclusion, the S. sinuosa fruit extract contains seven phenolic acids that can bind to HSA. Five of them, namely chlorogenic acid, caffeic acid, syringic acid, 2-hydroxycinnamic acid, and sinapinic acid, have potential to play a role in antiglycation.
Keywords: Antiglycation, Sararanga sinuosa, Molecular docking, Pandan anggur, Phenolic acids.